실버 파우더 형상에 따른 감광성 실버페이스트의 물성 연구 - 남수용; Su Yong Nam (한국화상학회지, 2015)
본 연구에서는 크기와 형상이 서로 다른 4가지 실버 파우더를 이용하여 감광성 실버 페이스트를 제조 하였다. 제조된 실버 페이스트의 레올로지 특성 및 터치패널용 전도성 미세패턴 구현을 검토하였다. 그리고 건조방식에 따른 전도성도 평가하였다. 그 결과 실버 파우더의 평균입자 크기는 D50=0.8∼1.0㎛이 가장 낮은 저항치를 얻을 수 있었고, 또한 패턴의 Sharpness도 가장 우수함을 알 수 있었다. 건조방식은 예비건조 및 후건조를 IR/IR방식으로 진행한 것이 가장 낮은 저항치를 얻을수있었다. In this research, four different silver powders with specific sizes and shapes were used in order to produce photosensitive silver paste. The produced silver paste was checked in order to see whether its rheological properties and its micro-conductive pattern specific to the touch panel were well embodied. Moreover, the conductance of the paste, with reference to its drying system, was evaluated. As a result, the lowest resistance was achieved when the particle mean diameter was D50=0.8∼1.0㎛, which also produced the highest pattern sharpness. The drying system where IR/IR method was used for both pre-drying and post-drying processes resulted in the lowest resistance.